Gain enhancement of dielectric resonator loaded wave-guide antennas with dielectric overlays - Hakkak, M.; Ameri Mahabadi, H. (1992)
The gain characteristics of a dielectric resonator loaded coaxial probe fed circular waveguide antenna (DRLWA) with overlaying parasitic discs have been investigated experimentally. Results indicate that, when properly spaced, the overlays can enhance the gain by more than 6 dB.